Hospital emergency department visits by ambulance for nontraumatic tooth pain in the USA - Shenkin JD; Warren J; Spanbauer C; Okunseri E; Szabo A; Okunseri C (Dove Medical Press, 2018)
Jonathan D Shenkin,1 John Warren,2 Charles Spanbauer,3 Elaye Okunseri,4 Aniko Szabo,3 Christopher Okunseri4 1Department of Health Policy and Health Services Research, Boston University School of Dental Medicine, Boston, MA, USA; 2Department of Preventive and Community Dentistry, University of Iowa, College of Dentistry and Dental Clinics, Iowa City, IA, USA; 3Division of Biostatistics, Institute of Health and Society, Medical College of Wisconsin, Milwaukee, WI, USA; 4Department of Clinical Services, Marquette University School of Dentistry, Milwaukee, WI, USA Objective: This study examined the prevalence of ambulance use for nontraumatic tooth pain (NTP) visit to emergency departments (EDs) and the factors associated with ambulance use for NTP in the USA. Materials and methods: Data from the National Hospital Ambulatory Medical Care survey conducted in the USA from 2003 to 2012 were analyzed. Descriptive statistics were obtained, and multivariable logistic regression was used to determine associations with ambulance use for NTP. Results: The total proportion of ED visits due to NTP by ambulance was 1.1%, lowest in 2008 (0.43%) and highest in 2011 (2.28%). The proportion of ED visits due to NTP by ambulance was highest among public insurance enrollees (1.9%), Hispanics (2.3%) and those aged 45–64 years (2.7%). In the multivariable analysis, those aged 45–64 years had approximately four times higher odds of an ED visit for NTP by ambulance compared to those aged 25–44 years. Conclusion: This study demonstrates that transport to EDs by ambulance for NTP does occur at a measurable rate and adults aged 45–64 years had significantly higher odds of ED visits for NTP by ambulance. Keywords: adults, dental caries, toothache, emergency department services